The Christ who Embraces : An Orthodox Theology of Margins - Joseph, Jacob, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2025)
Jacob Joseph's book, The Christ who Embraces: An Orthodox Theology of Margins , explores the intersection of Orthodox Christian mission and caste dynamics among St. Thomas/Syrian/Orthodox Christians in India. It defines a liturgical touch or embrace in the context of 'untouchability,' where people identify as equal without discrimination, reflecting the inseparable unity of Christ's transcendental (divine) and immanent (human) nature. See Less